2018
DOI: 10.1186/s12881-018-0646-1
|View full text |Cite
|
Sign up to set email alerts
|

Cenani-Lenz syndactyly syndrome - a case report of a family with isolated syndactyly

Abstract: BackgroundCenani-Lenz Syndactyly (CLS) syndrome is a rare autosomal recessive disorder characterized by syndactyly and oligodactyly of fingers and toes, disorganization and fusion of metacarpals, metatarsals and phalanges, radioulnar synostosis and mesomelic shortness of the limbs, with lower limbs usually being much less affected than upper limbs.Case presentationwe report here two patients, born to consanguineous Sri Lankan parents, present with bilateral postaxial oligodactyly limited to upper limbs. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Consistently, variable mutations affecting the LRP4 may cause distinct phenotypes, including either SOST2, CLSS or congenital myasthenia (MIM 616304) (Li et al, 2010; Ohkawara et al, 2014; Park et al, 2010). Recently, a few cases of isolated syndactyly have been also described (Hettiaracchchi et al, 2018; Sukenik‐Halevy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, variable mutations affecting the LRP4 may cause distinct phenotypes, including either SOST2, CLSS or congenital myasthenia (MIM 616304) (Li et al, 2010; Ohkawara et al, 2014; Park et al, 2010). Recently, a few cases of isolated syndactyly have been also described (Hettiaracchchi et al, 2018; Sukenik‐Halevy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current knowledge, additional features of the syndrome involve mild facial dysmorphism, renal hypoplasia or renal agenesis (Li et al, 2010; Stals et al, 2018; Temtamy, Ismail, & Nemat, 2003). Recently, Sukenik‐Halevy et al 2018 and Hettiaracchchi et al 2018 identified compound heterozygous p.Asp1403His, p.Gln1564Lys, and homozygous p.Ile450Val novel mutations affecting the LRP4 gene in two families with allegedly isolated syndactyly. According to the authors, the described LRP4 variants gave rise neither to SOST2, nor CLSS, but resulted in a new nonsyndromic limb phenotype comprising isolated form of hand syndactyly (Hettiaracchchi et al, 2018; Sukenik‐Halevy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oligosyndactyly is one of the syndactyly phenotypes and it is a frequent feature in several syndromes, namely, CLS syndrome, fibular aplasia, tibial campomelia and oligosyndactyly (FATCO) syndrome, fibular hemimelia (FH), Cornelia de Lange (CdL) syndrome and chromosome 2q35 duplication syndrome. A comprehensive literature review revealed the rare association of syndactyly with hypothyroidism in CLS syndrome [ 19 , 20 ]. The genetic etiology of this is mapped to CLC1 locus on chromosome region 11p11.2-q13.1 and is thought to result from mutations in the LRP4 gene [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review revealed the rare association of syndactyly with hypothyroidism in CLS syndrome [ 19 , 20 ]. The genetic etiology of this is mapped to CLC1 locus on chromosome region 11p11.2-q13.1 and is thought to result from mutations in the LRP4 gene [ 20 ]. CLS syndrome is characterized by syndactyly and oligodactyly of fingers and toes, facial dysmorphism, renal anomalies and congenital hypothyroidism [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation